Pediatric Endotracheal Tube Cuff Pressures During Aeromedical Transport. Issue 1 (January 2016) - Orsborn, Jonathan; Graham, James; Moss, Michele; Melguizo, Maria; Nick, Todd; Stroud, Michael
Abstract : Objectives: Cuffed endotracheal tubes (ETTs) are frequently used in children, allowing fewer air leaks and helping prevent ventilator-associated pneumonia. Tracheal mucosal perfusion is compromised at an ETT cuff pressure (ETTCP) of 30 cm H2 O with blood flow completely absent above 50 cm H2 O. Our objective was to compare multiple pediatric-sized ETTCPs at ground level and various altitudes during aeromedical transport. Methods: Simulating the transport environment, 4 pediatric-sized mannequin heads were intubated with appropriately sized cuffed ETTs (3.0, 4.0, 5.0, 6.0) and transported by helicopter or nonpressurized fixed-wing aircraft 20 times each. The ETTCP was set to 10 cm H2 O before transport, and the pressure was measured with a standard manometer at 1000-ft intervals until reaching peak altitude or CP greater than 60 cm H2 O. Ground elevation ranged from 400–650 ft mean sea level (MSL) and peak altitude from 3500 to 5000 ft MSL. Results: Increased altitude caused a significant increase in ETTCP of all ETT sizes ( P < 0.001). However, there is no statistical difference in pressures between ETT sizes ( P = 0.28). On average, ETTCP in 3.0, 4.0, and 6.0 ETTs surpassed 30 cm H2 O at approximately 1500 ft MSL and 50 cm H2 O at approximately 2800 ft MSL. In the 5.0 ETT, the CP reached 30 cm H2 O at 2000 ft MSL and 50 cm H2 O at 3700 ft MSL. Conclusions: The ETTCP in pediatric-sized ETTs regularly exceed recommended pressure limits at relatively low altitudes. There is no additional pressure increase related to ETT size. This has the potential to decrease mucosal blood flow, possibly increasing risk of subsequent tracheal stenosis, rupture, and other complications.